Ethical and Analytic Challenges With Genomic Sequencing of Relapsed Hematologic Malignancies Following Allogeneic Hematopoietic Stem-Cell Transplantation. (2021) - Marwa, Bilal; Krueger, Joerg; Stephenson, Elizabeth A.; Davidson, Scott; Allan, David; Knoppers, Bartha; Zawati, Ma'n; Sullivan, Patrick; Shlien, Adam; Malkin, David; Fernandez, Conrad V.; Villani, Anita
Abstract : The implementation of precision medicine and next-generation sequencing technologies in the field of oncology is a novel approach being more widely studied and used in cases of high-risk primary and recurrent malignancies. Leukemias are the second most common cause of cancer-related mortality in children and the sixth most in adults. Relapsed leukemia represents a major component of the population that may benefit from genomic sequencing. However, ethical and analytic challenges arise when considering sequencing of biologic samples obtained from patients with relapsed leukemia following allogeneic hematopoietic stem-cell transplantation. Blood from the recipient after transplantation would include donor-derived cells and thus, genomic sequencing of recipient blood will interrogate the donor germline in addition to the somatic genetic profile of the leukemia cells and the recipient germline. This is a situation for which the donor will not have typically provided consent and may be particularly problematic if actionable secondary or incidental findings related to the donor are uncovered. We present the challenges raised in this scenario and provide strategies to mitigate this risk.